Iterated Function Systems with the Weak Average Contraction Conditions. Issue 2 (3rd July 2019) - Ehsani, A.; Ghane, F. H.
Abstract: This paper concerns the chaos game of random iterated function systems. We consider a random iterated function system IFS( ) generated by a finite family of Lipschitz maps on a compact ball of ℝ n with the weak average contraction condition and show that it admits a quasi-attractor satisfying the deterministic chaos game. In particular, these properties are preserved under small perturbations of the iterated function system IFS( ) with respect to the Lipschitz topology.